2012
DOI: 10.1007/s10964-012-9836-x
|View full text |Cite
|
Sign up to set email alerts
|

Motives for Using Facebook, Patterns of Facebook Activities, and Late Adolescents’ Social Adjustment to College

Abstract: Previous studies have confirmed that Facebook, the leading social networking site among young people, facilitates social connections among college students, but the specific activities and motives that foster social adjustment remain unclear. This study examined associations between patterns of Facebook activity, motives for using Facebook, and late adolescents' social adjustment to the college environment. Anonymous self-report survey data from 193 mostly European American students (M age = 20.32; 54 % female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
148
2
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(175 citation statements)
references
References 54 publications
10
148
2
15
Order By: Relevance
“…In contrast, a study of American undergraduate students suggests that use of social networking sites has the potential to facilitate the transition from secondary school to college. Students who reported greater attempts to form new relationships through social networking sites were less socially adjusted and reported more loneliness than their peers who used social networking sites to maintain already existing relationships (Yang & Brown, 2013). However, most students in this study reported using social networking sites to maintain relationships with pre-collegiate friends rather than to establish new relationships (Yang & Brown, 2013).…”
Section: Social Competencementioning
confidence: 65%
See 2 more Smart Citations
“…In contrast, a study of American undergraduate students suggests that use of social networking sites has the potential to facilitate the transition from secondary school to college. Students who reported greater attempts to form new relationships through social networking sites were less socially adjusted and reported more loneliness than their peers who used social networking sites to maintain already existing relationships (Yang & Brown, 2013). However, most students in this study reported using social networking sites to maintain relationships with pre-collegiate friends rather than to establish new relationships (Yang & Brown, 2013).…”
Section: Social Competencementioning
confidence: 65%
“…However, most students in this study reported using social networking sites to maintain relationships with pre-collegiate friends rather than to establish new relationships (Yang & Brown, 2013). But no matter the motivation, the more students engaged in online interactions through social networking sites the better their social adjustment and less their sense of loneliness (Yang & Brown, 2013).…”
Section: Social Competencementioning
confidence: 83%
See 1 more Smart Citation
“…The literature on Facebook use and HE covers a range of topics, from the use of Facebook for and to support teaching and learning (CLEX, 2009;Greenhow & Robelia, 2009;Manca & Ranierit, 2013;Mazer et al, 2007), the relationship between staff and student use of the site (Hewitt & Forte, 2006), the impact of Facebook on academic achievement (Kirschner & Karpinski, 2010;Karpinski, 2009;Pasek, 2009) and the social implication of using Facebook at university (Ellison et al, 2007;Madge et al, 2009;Pemepek et al, 2009;Steinfield et al, 2008;Yang & Brown, 2013). The use of Facebook for learning and its educational value has received much attention (see review by Manca & Ranierit, 2013).…”
Section: Facebook In the Lives Of Undergraduate Studentsmentioning
confidence: 99%
“…Pesquisas sobre o comportamento dos usuários em relação as suas interações, tanto com cunho tecnológico quanto comportamental, foram e têm sido realizadas para várias redes tais como Facebook [79,73,80,81,82,83], Flirk [84], Twitter [77,85]e Google+ [86]. A análise da navegação de usuários nessas redes também é estudada por [87].…”
Section: Aspectos Da Comunicação Socialunclassified